Disability and physical activity in people with chronic disease receiving physiotherapy. A prospective cohort study - Tønning, Lisa U.; Mechlenburg, Inger; Christiansen, David H.; Andersen, Nils-Bo V.; Stabel, Henriette H.; Pedersen, Asger R.; Nielsen, Jørgen F.; Grimm, Bernd; Næss-Schmidt, Erhard (Frontiers in Sports and Active Living, 2022)
Chronic disease affects patients' disability and participation in activities of daily living. Longitudinal information on disability and physical activity is generally scarce in patients with chronic disease. The current study aimed to investigate if self-reported disability and physical activity changed in patients with chronic disease receiving physiotherapy. Furthermore, the aim was to assess if an improvement in self-reported disability was related to an increase in objectively measured physical activity and if an aggravation in self-reported disability was related to a decrease in physical activity. Seventy patients with either multiple sclerosis, Parkinson's disease, rheumatoid arthritis or stroke receiving free of charge physiotherapy were tested at baseline and 1 year later. Disability was measured with the self-reported modified Ranking Scale-9 Questionnaire and physical activity was objectively measured using tri-axial accelerometry. Neither self-reported disability nor physical activity changed among patients receiving 1 year of free of charge physiotherapy at group level. Furthermore, self-reported change of disability was not expressed with changes in objectively measured physical activity, indicating that the two measures represent two different constructs.